Potential Impacts of Climate Change on Waste Management in Ilorin city Nigeria (Global Journal of Human-Social Science, 2012)
Ilorin is one of the major cities in Nigeria today and its growing capacity in both socio-economic affiliations is commendable However the city is potently polluted with heaps of refuse that are occasionally caused traffic hold-up in places in the urban centre A lot of health incidence resulting from water air and pest borne diseases are not uncommon within areas where prevalence of effluents prevailed Current problems of poor waste management upon the government efforts is as a result of the potential impacts of climate change on the natural world and with wide effects resulting from these changes has its implications in Ilorin city This work examines the management of waste in city of Ilorin which has been the sole responsibility of the Kwara State Environmental Protection Agency KWEPA and other health management sectors Worldly wise there are evidences that climate change and its due at least in part to human activities gives rise to emissions of Green house gases GHG s which invariably is disturbing the world Wilby 2003 Over the last 100 years the average temperature of the air near the Earth s surface has risen a little less than 1 Celsius 0 74 0 18 C or 1 3 0 32 Fahrenheit Does not seem all that much These changes could have significant impacts on a range of social economic and environmental processes as well as waste management in the areas selected for this study Two hundred 200 questionnaires were randomly distributed to member of households on wards basis in Ilorin An addition of Fifty 50 questionnaires was also distributed to agencies that control and manage waste while their contributions to waste control in the state were assessed Suggestions were put forward for all to remain alert and that in the future we may experience higher temperatures extreme decay and more environmental problems except if proper precautions are taken
Keywords: Climate Change; Potential impacts; Green house gases; Effluents; Waste management